2014
DOI: 10.1111/jpc.12674
|View full text |Cite
|
Sign up to set email alerts
|

Educational, developmental and psychological outcomes of resettled refugee children in Western Australia: A review of School of Special Educational Needs: Medical and Mental Health input

Abstract: Aim There are limited data regarding the educational backgrounds and associated psychological and developmental outcomes of refugee children resettling in Western Australia (WA). The WA paediatric Refugee Health Service (RHS) revised its first consult questionnaire (August 2011) to increase educational and psychosocial documentation, concurrent with engagement of a School of Special Educational Needs: Medical and Mental Health (SSEN: MMH) liaison teacher. This study aims to utilise these data to increase under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 30 publications
2
46
0
2
Order By: Relevance
“…28 Three studies reported that family cohesion and supportive home environment were associated with better secondary school outcomes (particularly for girls). 6,24,30 Two studies reported on the association between parental physical and mental health and secondary school outcomes, with 1 finding a positive association 40 and the other finding no association. 30 …”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Three studies reported that family cohesion and supportive home environment were associated with better secondary school outcomes (particularly for girls). 6,24,30 Two studies reported on the association between parental physical and mental health and secondary school outcomes, with 1 finding a positive association 40 and the other finding no association. 30 …”
Section: Depressionmentioning
confidence: 99%
“…A single Australian study reported on the prevalence of sensory impairment (vision, hearing) and developmental delay in a mixed cohort of 332 children attending a refugee health clinic: 7.5% had a visual impairment, 3.3% had a hearing impairment, and 6.9% had developmental delay, most commonly language (5.7%) or gross motor (2.1%). 24 Two studies from the United States 20 and Sweden 14 provided information on intellectual impairment, using cognitive testing to investigate the impact of trauma on intelligence. These studies reported that among more than 400 Iraqi-background and African American adolescents, half (49.4%-56.3%) had low or borderline IQ scores on the Wechsler Intelligence Scales for Children (WISC).…”
Section: Prevalence Of Learning Problemsmentioning
confidence: 99%
“…When supporting young people from an asylum seeker background, there is a need to recognise that this is a population who have been observed to express their distress through somatic symptoms (Mace, Mulheron, Jones, & Cherian, 2014;Mann & Fazil, 2006, p. 59). The Diagnostic and Statistical Manual of Mental Disorders, 5 th edition describes Somatic Symptom Disorder as typically having ì...multiple, current, somatic symptoms that are distressing or result in significant disruption of daily lifeî (American Psychiatric Association, 2013, p. 311).…”
Section: Medical: Traumamentioning
confidence: 99%
“…In resettlement countries such as Australia, school is one of the primary places where newly arrived refugee students will connect with their community, build relationships, and establish a sense of belonging in their new country (Woods, 2009;Matthews, 2008; Correa--Velez, Gifford, & Barnett, 2010;Mace, Mulheron, Jones, & Cherian, 2014;de Heer, Due, & Riggs, 2016). As such, school belonging plays a crucial role in establishing a sense of social inclusion, positive wellbeing and the development of peer relationships for refugee young people from the beginning of their resettlement (Correa--Velez, et al, 2010;de Heer, et al, 2016; Woods, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While only a proportion of these young people and their families will be moved to a resettlement country, it is nevertheless vitally important that resettlement countries have an evidence base upon which to draw when providing settlement services and support to young people with refugee backgrounds. This is an Author's Accepted Manuscript of a paper published in the Educational and Developmental Psychologist Copyright Cambridge University Press DOI: 10.1017/edp.2016.9In resettlement countries such as Australia, school is one of the primary places where newly arrived refugee students will connect with their community, build relationships, and establish a sense of belonging in their new country (Woods, 2009;Matthews, 2008; Correa--Velez, Gifford, & Barnett, 2010;Mace, Mulheron, Jones, & Cherian, 2014;de Heer, Due, & Riggs, 2016). As such, school belonging plays a crucial role in establishing a sense of social inclusion, positive wellbeing and the development of peer relationships for refugee young people from the beginning of their resettlement (Correa--Velez, et al, 2010;de Heer, et al, 2016; Woods, 2009).…”
mentioning
confidence: 99%